Persepsi anak terhadap dokter gigi pada Rumah Sakit Gigi Mulut Halimah Dg. Sikati di Makassar(Children’s perception of their dentist at Halimah Dg.Sikati Dental Hospital in Makassar) - Ayub Irmadani Anwar (Journal of Dentomaxillofacial Science, 2014)
Management of child behavior begins when the children enters the dental environment and continues until they leaveit. Fear of dentist and dental treatment have been considered a major hindrance to provide a quality dental services.Establish a friendly relationship with children is important for dentist to combat patient’s fears and to deliver effectiveand efficient treatment. The aim of this study was to assess children’s feelings and attitudes toward their dentist inHalimah Dg. Sikati Dental Hospital. A questionnaire designed to evaluate children’s attitudes and preferences towarddentists was completed by 45 children (29 females, 19 males) who attended the hospital. It showed 80% of the subjectreported that they had been to the dentist before; 84.4% report liked their visit, and 8.9% were afraid. A 93,3% of thechildren preferred their dentist to wear a white coat, while 80% preferred them to wear a mask, 82.2% preferred tobe treated by a female dentist, while 77,8% reported that their sibling had a pleasant perception. 80% of the childrenpreferred that their dentist wear the formal attire. Fear of local anesthesia and tooth extraction were the most commonreasons cited for not liking dental treatment. It was concluded that children have strong perceptions and preferences regarding their dentists.